7x-83=57-3x

Simple and best practice solution for 7x-83=57-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-83=57-3x equation:


Simplifying
7x + -83 = 57 + -3x

Reorder the terms:
-83 + 7x = 57 + -3x

Solving
-83 + 7x = 57 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-83 + 7x + 3x = 57 + -3x + 3x

Combine like terms: 7x + 3x = 10x
-83 + 10x = 57 + -3x + 3x

Combine like terms: -3x + 3x = 0
-83 + 10x = 57 + 0
-83 + 10x = 57

Add '83' to each side of the equation.
-83 + 83 + 10x = 57 + 83

Combine like terms: -83 + 83 = 0
0 + 10x = 57 + 83
10x = 57 + 83

Combine like terms: 57 + 83 = 140
10x = 140

Divide each side by '10'.
x = 14

Simplifying
x = 14

See similar equations:

| (6.78)(0.4-X)=2X | | 20x^2+240x-27=0 | | 4x+3-10=6x-2 | | (6.78)(0.4-X)= | | (-7c^2-2c-5)+(9c-6)-(16c^2+3)+(-9c^2-7c+7)= | | 110+6x=8x+114 | | y/4= | | 2cos3pi/8*cospi/8 | | 3v-9=33 | | 18*3.14+6*3.14x=420 | | 2cos3pi/8 | | 1.67/0.75 | | F(x)=11x^2+13x | | 2tanx+9=7 | | -5/3X-1/4=-1/6X-1/8 | | 5n^2+8n-10=0 | | 82-62=10x-15x | | (n/4)-5=8 | | 5c-13=8-2c | | -4(0)+2y=7 | | Sec^2x=4tan^2x | | -4x+2(0)=7 | | 4m+3=16 | | 2(-2)+3y=-4 | | 2x+3(0)=-4 | | 3(y-6)-2(5+3y)=5 | | 2(y+6)+1=3y+12-y | | X*4+6=20 | | 8(-1.25)-3y=-10 | | 2x^2-5x=-2is | | 8x-3(0)=-10 | | 3/1*8/9*4/11 |

Equations solver categories